Bone morbidity in pediatric acute lymphoblastic leukemia - Moon Bae Ahn; Byung-Kyu Suh (Korean Society of Pediatric Endocrinology, 2020)
Acute lymphoblastic leukemia (ALL), currently the most common pediatric leukemia, has a high curability rate of up to 90%. Endocrine disorders are highly prevalent in children with ALL, and skeletal morbidity is a major issue induced by multiple factors associated with ALL. Leukemia itself is a predominant risk factor for decreased bone formation, and major bone destruction occurs secondary to chemotherapeutic agents. Glucocorticoids are cornerstone drugs used throughout the course of ALL treatment that exert significant effects on demineralization and osteoclastogenesis. After completion of treatment, ALL survivors are prone to multiple hormone deficiencies that eventually affect bone mineral accrual. Dual-energy X-ray absorptiometry, the most widely used method of measuring bone mineral density, is used to determine the presence of childhood osteoporosis and vertebral fracture. Supplementation with calcium and vitamin D, administration of pyrophosphate analogues, and promotion of mobility and exercise are effective options to prevent further bone resorption and fracture incidence. This review focuses on addressing bone morbidity after pediatric ALL treatment and provides an overview of bone pathology based on skeletal outcomes to increase awareness among pediatric hemato-oncologists and endocrinologists.